High Levels of miR-483-3p Are Present in Serum Exosomes Upon Infection of Mice With Highly Pathogenic Avian Influenza Virus - Maemura, Tadashi; Fukuyama, Satoshi; Kawaoka, Yoshihiro (Frontiers in Microbiology, 2020)
Exosomes, the extracellular vesicles that contain functional proteins and RNAs, regulate cell-cell communication. Recently, our group reported that levels of various microRNAs (miRNAs) in bronchoalveolar lavage fluid exosomes were highly increased in influenza virus-infected mice and that one of those miRNAs, miR-483-3p, was involved in the potentiation of the innate immune responses to influenza virus infection in mouse type II pneumocytes. Here, we evaluated exosomal miR-483-3p levels in the serum of influenza virus-infected mice and found that miR-483-3p levels were significantly increased during infection with a highly pathogenic avian H5N1 influenza virus. Moreover, miR-483-3p-enriched exosomes derived from type II pneumocytes potentiated the expression of proinflammatory cytokine genes in vascular endothelial cells. Our findings suggest that serum exosomal transfer of miR-483-3p might be involved in the inflammatory pathogenesis of H5N1 influenza virus infection.